The Potential Value of m6A RNA Methylation in the Development of Cancers Focus on Malignant Glioma - Chen, Fan; Xie, Xuan; Chao, Min; Cao, Haiyan; Wang, Liang (Frontiers in Immunology, 2022)
N6-methyladenosine (m6A) RNA methylation is an epigenetic modification that has emerged in recent years and has received increasing attention as the most abundant internal RNA modification in eukaryotic cells. m6A modifications affect multiple aspects of RNA metabolism, and m6A methylation has been shown to play a key role in the development of multiple cancers through a variety of mechanisms. This review summarizes the mechanisms by which m6A RNA methylation induced peripheral cancer cell progression and its potential role in immune cell infiltration in the glioblastoma microenvironment and novel immunotherapy. Assessing the pattern of m6A modification in glioblastoma will help to enhance our understanding of microenvironmental infiltration and novel immunotherapy, and contribute to formulating the strategies of immunotherapy.